Quality of life after thyroidectomy in patients with nontoxic nodular goiter: A prospective cohort study. Issue 11 (4th September 2017) - Sorensen, Jesper Roed; Watt, Torquil; Cramon, Per; Døssing, Helle; Hegedüs, Laszlo; Bonnema, Steen Joop; Godballe, Christian
Abstract: Background: Using the thoroughly validated Thyroid‐Related Quality‐of‐Life Patient‐Reported Outcome (ThyPRO) questionnaire, the purpose of this study was to investigate changes in disease‐specific quality of life (QOL) after surgical treatment in patients with benign nontoxic multinodular goiters. Method: Patients with goiters scheduled for thyroid surgery (n = 106) and individuals from the general population (n = 739) were studied. The ThyPRO data before, 3 months, and 6 months after surgery were compared with normative scores from the general population using a linear mixed model and t tests. Results: Before surgery, patients with goiters experienced poorer scores on all scales compared to the general population. After surgery, moderate to large improvements were seen in goiter symptoms, tiredness, anxiety, and overall QOL. After surgery, all scales returned to values equal to the general population. The degree of anxiety was, in fact, lower than in the general population. Conclusion: Thyroid surgery leads to significant benefit among patients with benign nontoxic goiters by restoring QOL equal to that in the general population.